Potential applications of topical oxygen therapy in dermatology - Luigi Bennardo; Ester Del Duca; Stefano Dastoli; Giusy Schipani; Elisabetta Scali; Martina Silvestri; Steven Nisticò (Mattioli1885, 2018)
Background: Topical oxygen therapy is a cosmetic procedure that is becoming more and more popular in dermatology; however, only a few articles on this topic are present in the literature. In this work we report our group experience with oxygen therapy as an adjuvant treatment in various dermatological conditions. Methods: Four studies were conducted. In the first study we used vehiculated oxygen therapy for diseases that cause hair loss. In the second study oxygen was used in the treatment of mild acne. In the third study moderate acne was treated with topical oxygen. In the fourth study chronic dermatological conditions such as psoriasis and atopic dermatitis were treated with this procedure. Results: In studies 1 and 2 the outcomes in groups who used topical oxygen therapy as an adjuvant treatment were better than in the groups that did not use it. Studies 3 and 4 also showed very good results, but no control groups were present in the study. Conclusion: Topical oxygen therapy was useful in the treatment of hair loss conditions, mild and moderate acne, and in chronic cutaneous diseases, showing effectiveness as a support therapy in all of these conditions. Further and larger studies should be conducted to better evaluate its effectiveness in dermatological conditions.